Pengaruh Penerapan Algoritma Clustering COEEC Terhadap Kinerja Protokol Routing DSR di Jaringan MANET - Lalu Ikhwan Rosadi; Andy Hidayat Jatmika; Sri Endang Anjarwani (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2019)
MANET can be used as an alternative communication solution because it is mobile, meaning that it does not have a fixed infrastructure. MANET implementation can use routing protocols, one example of which is Dynamic Source Routing (DSR). DSR routing protocol works when there is a request for sending packets from the source node to the destination node using two main mechanisms namely, route discovery and route maintenance. Route discovery occurs when the process of sending data from the source node to the destination node by performing a flooding mechanism to the neighboring node. If there is an excessive flooding mechanism, it can cause an increase in routing overhead on the DSR routing protocol. So to overcome these problems clustering is done by utilizing the Overhead Energy Efficient Cluster (COEEC) algorithm on the DSR routing protocol. The results of the addition of clusters in the DSR routing protocol with the COEEC algorithm can increase throughput performance by 43% and 31%, then an increase in the average end to end delay of 0.005% and 0.01%, then the packet delivery ratio parameter increases